The Epidemiology of Bloodstream infection (BSI) in Nopparat Rajathanee Hospital, 2018 - Attapornkusol, Pornpimol; Khumsri, Jiraporn; Khuanped, Sinjai; Wattanakul, Naiyana; Aiumlaor, Pornapa; Tantilipikara, Peangpim; Samanmit, Yuthana; Sawanpanyalert, Narumol (Journal of The Department of Medical Services, 2021)
Background : Blood stream infection; BSI is a major burden of health problems that contributed to high mortality. It can be classified into 2 types, community-acquired; CA-BSI and hospital-acquired; HA-BSI. Previous study presented the CA-BSI and HA-BSI definition which the duration time is several of them. CA- BSI was called present on admission; POA which followed US-CDC 2017 definition. POA is the patients who had length of stay less than 2 days. However, these patients may be readmitted, defined as ones who had length of stay more than 2 days of previous admission and discharged within 14 days before the date of event. Interestingly, the infection time frame of POA was not mentioned for HA-BSI. Objective : To explore the BSI patients following US-CDC 2017 definition. Method : Medical records of hospitalized patients during January to December 2018 who had at least one of positive blood cultures were review. Data was reviewed by infection control nurse team to identify blood culture results that were met the US-CDC 2017 definition for bloodstream infection. Results : A total of 593 patients with at least one positive blood culture results were reviewed, 479 episodes (86.7%) were CA-BSIs, 97 episodes (16.4%) were HA-BSIs and 17 episodes (2.9 %) met POA. Primary BSI of POA was 58.8%, which the median (Q1, Q3) of the admission days before readmission were 7 (5, 16) days. The diagnoses of them from previous admission were urinary tract infections (23.5%) and pneumonia (17.6%) which the most of organisms were Escherichia coli (47.1%). Moreover, 62.5% of them found antimicrobial resistance bacteria. Conclusions : Our study demonstrated that among patients who had bloodstream infections, 2.9% was POA. Most of these patients were readmitted within infectious diseases from previous admission. Our data may be beneficial for discharge planning for patient-at-risk. POA definition may be considered for these kinds of patients.